Managing engineering and technology - Morse, Lucy C. (Pearson, 2014)
Managing Engineering and Technology is ideal for courses in Technology Management, Engineering Management, or Introduction to Engineering Technology. This text is also ideal for engineers, scientists, and other technologists interested in enhancing their management skills.